The Developments and Trends of the Agricultural Sector in Greece - Papaelias, Theodore; Hyz, Alina; Panagou, Vasilios (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
The purpose of this paper is to analyse the changes in the efficiency of Greek agriculture production in the period 1911-2011, and to estimate the trends that emerged, especially after the country joined the E.U. in 1981. The applied methodology uses both quantitative methods (econometric approach), as well as the social-historical interpretation of rural policy, as established in the last hundred years.The paper is organized as follows: in the first section we review the evolutions in the accumulation of wealth and the income. In the second section we describe our methodology and data sources used in the analysis. Next, we present and discuss the results. We conclude with some proposals which stem from the analysis.